Immobilization of peroxidase from fresh horseradish extract for anthraquinone dye decolorization - Nataša Ž. Šekuljica; Nevena Ž. Prlainović; Nevena M. Lukić; Aleksandra M. Jakovljević; Sanja Ž. Grbavčić; Dušan Ž. Mijin; Jugović Zorica D. Knežević (Zaštita Materijala)
Synthetic dyes are used in all sectors of industry and represent a serious ecological problem. By the presence, anthraquinone dyes are right after the azo dyes. Unlike azo, anthraquinone dyes are considerably harder to degrade due to the presence of coupled aromatic rings in their structure. Horseradish peroxidase (HRP) proved to be an efficient and ecologically acceptable solution for synthetic dyes decolonization. For that reason, feasibility of peroxidase from fresh horseradish extract application in anthraquinone dye decolonization was the object of this research. Unpurified peroxidase (1.5 mg mL-1), was immobilized onto fumed silica by adsorption. In order to optimize the decolonization of anthraquinone dye Acid Violet 109 (AV 109) 0.1 IU of obtained immobilized HRP was applied in a batch reactor. Under the optimal conditions (pH 4.0, dye concentration 30 mg L-1, hydrogen peroxide concentration 0.1 mM) 55.1 % of initial dye concentration was decolorized, within 30 min. In addition, compared to free enzyme, immobilized HRP showed higher resistance towards inhibitory influence of the dye and hydrogen peroxide.